Pacific 360° - Perry, Roland, 1946- (Sydney : Hachette Australia, 2012)
PACIFIC 360 is a sweeping national narrative that looks for the first time at the Pacific War in its entirety, bringing together the story behind one of the most crucial times in Australian history. On 7 December 1941, Australia was pushed to centre stage as Japan entered World War II and began the offensive which triggered the Pacific War.
"Australia's battle for survival in World War II"--Dust cover.
Includes bibliographical references (p. 466-484) and index.
General.
Keywords: World War, 1939-1945 -- Participation, Australian; World War, 1939-1945 -- Campaigns -- Pacific Ocean; World War, 1939-1945 -- Pacific Area; Australia -- History -- 1939-1945.; Australian